Penghentian Penuntutan Perkara Penyalahgunaan Narkotika Sebagai Implementasi Restorative Justice pada Tahap Penuntutan (Studi Kasus di Kejaksaan Negeri Pasaman Barat) - Sayutis, Sayutis; Danil, Elwi; Yoserwan, Yoserwan (Universitas Ekasakti, 2024)
Crime or criminal act is a word that is familiar to the public. Crime is increasingly common in society and its presence is very disturbing to society, because the losses it causes are not only material losses, but also the loss of a person's soul or life. The provisions of Law Number 35 of 2009 concerning Narcotics (Narcotics Law) have also mentioned several terms that have the same essence as narcotics users themselves, including narcotics abusers, victims of abusers, former narcotics abusers and patients. There are examples of cases of implementing medical rehabilitation. and social issues regarding narcotics abuse in the jurisdiction of the West Pasaman District Prosecutor's Office. Where the West Pasaman District Prosecutor's Office stopped the prosecution or Restorative Justice of three narcotics case files with five suspects to undergo rehabilitation because the suspects were narcotics addicts, not dealers. The suspects are suspected of being users or addicts of class I narcotics, not methamphetamine, violating Article 127 paragraph (1) letter a of the Narcotics Law. The Problem Formulation is (1) How is the termination of prosecution of narcotics abuse cases as an implementation of restorative justice at the prosecution stage (Case Study at the West Pasaman District Prosecutor's Office) and (2) What are the obstacles in terminating the prosecution of narcotics abuse cases as an implementation of restorative justice at the prosecution stage (Case Study at the West Pasaman District Prosecutor's Office)?. The conclusions of this research are: (1) The implementation of restorative justice in cases of narcotics abuse has been implemented at the West Pasaman Prosecutor's Office for 4 (four) suspects. The West Pasaman Prosecutor's Office has implemented Prosecutor's Guidelines Number 18 of 2021 concerning the Resolution of Handling of Narcotics Cases through Rehabilitation with a Restorative Justice Approach as an implementation of the Prosecutor's Dominus Litis Principle. (2) In its implementation, of course the West Pasaman District Prosecutor's Office also experienced obstacles that affected the implementation of restorative justice in cases of criminal acts of narcotics abuse.